Respuesta :

ANSWER

The exact solution are:

[tex]y = \frac{ - 6 - 2 \sqrt{6} }{5} \: \: or \: \: y = \frac{ - 6 + 2 \sqrt{6} }{5} [/tex]

EXPLANATION

The given quadratic equation is

[tex] {(5y + 6)}^{2} = 24[/tex]

We use the square root method to solve for y.

We take square root of both sides to get:

[tex] \sqrt{{(5y + 6)}^{2}} = \pm\sqrt{24} [/tex]

This gives us:

[tex]5y + 6 = \pm 2 \sqrt{6} [/tex]

Add -6 to both sides to get:

[tex]5y = - 6 \pm 2 \sqrt{6} [/tex]

Divide through by 5:

[tex]y = \frac{ - 6 \pm2 \sqrt{6} }{5} [/tex]

[tex]y = \frac{ - 6 - 2 \sqrt{6} }{5} \: \: or \: \: y = \frac{ - 6 + 2 \sqrt{6} }{5} [/tex]